THE EFFECT OF PRICE, QUALITY OF PRODUCT AND QUALITY OF SERVICE TO PURCHASE INTEREST IN SEA TRANSPORTATION SERVICE AT PT. MARINATAMA GEMANUSA BATAM ROUTE TELAGA PUNGGUR - TG. PINANG. - Riky Aprianto; Lukmanul Hakim (EQUILIBIRIA, 2016)
This thesis titled "The Effect Of Price, Quality Of Product, And Quality Of Service To Purchase Interest In Sea Transportation Service At PT. MARINATAMA GEMANUSA BATAM Route Telaga Punggur – TG. Pinang ". The purpose of this study was to determine the influence of the implementation of price, qualiy of product and quality of service to purchase interest in sea transportation service at PT. Marinatama Gemanusa Batam. Data collected through questionnaires and conducted on 100 respondents. Analysis of the data in this study using SPSS version 20. The sample technique based on statistical and research estimated using the formula slovin with an error rate of 5 % - 10% and testing techniques of data used in this study include testing the validity of the factor analysis, Cronbach alpha reliability test . Classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis.Hypothesis testing using t test showed that the variable force price and service eis not effect on purchase interest and quality of product variables effect the variable purchase interest. Then through the F test can be seen that both the independent variables simultaneously effect the dependent variable. Figures adjusted R2 of 0.365 indicates that 36.5% price, quality of product, quality of service variable can be explained by the independent variables in the regression equation, while the remaining 63.5% is explained by other variables outside the two variables used in the study